The Untapped Genetic Reservoir: The Past, Current, and Future Applications of the Wild Soybean (Glycine soja) - Kofsky, Janice; Zhang, Hengyou; Song, Bao-Hua (Frontiers in Plant Science, 2018)
There is a considerable demand for crop improvement, especially considering the increasing growth of world population, continuing climatic fluctuations, and rapidly evolving plant pests and pathogens. Crop wild relatives hold great potential in providing beneficial alleles for crop improvement. Wild soybean, Glycine soja (Siebold & Zucc.), the wild ancestor to the domesticated soybean (Glycine max (L.) Merr.), harbors a high level of genetic variation. Research on G. soja has been largely devoted to understanding the domestication history of the soybean, while little effort has been made to explore its genetic diversity for crop improvement. High genomic diversity and expanded traits make G. soja populations an excellent source for soybean improvement. This review summarizes recent successful research examples of applying wild soybeans in dissecting the genetic basis of various traits, with a focus on abiotic/biotic stress tolerance and resistance. We also discuss the limitations of using G. soja. Perspective future research is proposed, including the application of advanced biotechnology and emerging genomic data to further utilize the wild soybean to counterbalance the rising demand for superior crops. We proposed there is an urgent need for international collaboration on germplasm collection, resource sharing, and conservation. We hope to use the wild soybean as an example to promote the exploration and use of wild resources for crop improvement in order to meet future food requirements.